Adiposity, physical activity and neuromuscular performance in children. Issue 18 (16th September 2016) - Haapala, Eero A.; Väistö, Juuso; Lintu, Niina; Tompuri, Tuomo; Brage, Soren; Westgate, Kate; Ekelund, Ulf; Lampinen, Eeva-Kaarina; Sääkslahti, Arja; Lindi, Virpi; Lakka, Timo A.
ABSTRACT: We investigated the associations of body fat percentage (BF%), objectively assessed moderate-to-vigorous physical activity (MVPA) and different types of physical activity assessed by a questionnaire with neuromuscular performance. The participants were 404 children aged 6–8 years. BF% was assessed using dual-energy x-ray absorptiometry and physical activity by combined heart rate and movement sensing and a questionnaire. The results of 50-m shuttle run, 15-m sprint run, hand grip strength, standing long jump, sit-up, modified flamingo balance, box-and-block and sit-and-reach tests were used as measures of neuromuscular performance. Children who had a combination of higher BF% and lower levels of physical activity had the poorest performance in 50-m shuttle run, 15-m sprint run and standing long jump tests. Higher BF% was associated with slower 50-m shuttle run and 15-m sprint times, shorter distance jumped in standing long jump test, fewer sit-ups, more errors in balance test and less cubes moved in box-and-block test. Higher levels of physical activity and particularly MVPA assessed objectively by combined accelerometer and heart rate monitor were related to shorter 50-m shuttle run and 15-m sprint times. In conclusion, higher BF% and lower levels of physical activity and particularly the combination of these two factors were associated with worse neuromuscular performance.